Thermal Emission‐Enhanced and Optically Modulated Radioisotope Thermophotovoltaic Generators. Issue 3 (10th December 2019) - Wang, Hongyu; Tang, Xiaobin; Liu, Yunpeng; Xu, Zhiheng; Yuan, Zicheng; Liu, Kai; Zhang, Zhengrong; Jiang, Tongxin
Abstract : Infrared radiation generated by high‐energy‐density radioisotope decay can be converted to electrical energy in radioisotope thermophotovoltaic (RTPV) generators. Thermal emission intensity and spectral properties have substantial implications in this thermal energy conversion process. To improve the performance of the RTPV generator, a silicone coating material is used as a thermal emission enhancer, and SiO2 is used as a filter. The silicone coating has excellent thermal emissivity at high temperatures. The SiO2 filter is used for optical modulation during the thermal energy conversion process. The heat transfer optimization problem caused by the internal temperature distribution of the system is discussed. Compared with the experimental model before optimization, the output power of the RTPV generator increased by 126% obtains an open‐circuit voltage of 2.64 V, an electric power of 89.88 mW, and an energy conversion efficiency of 5.62%. The RTPV generator is expected to be a potential candidate for energy supply in extreme environments. Abstract : Herein, the radioisotope thermophotovoltaic (RTPV) effect is studied. The thermal emission enhancement of the silicone coating is discussed, and the SiO2 filter is used to regulate the infrared radiation. The results show that the synergistic effect of the silicone coating and the SiO2 filter significantly increases the output power of the RTPV generators.